Comparison of the World Pharmacopoeias’ Requirements for the Quality of Cell Lines - M. A. Vodyakova; A. R. Sayfutdinova; E. V. Melnikova; Yu. V. Olefir (Биопрепараты: Профилактика, диагностика, лечение, 2020)
The cell line is one of the necessary components of a biomedical cell product (BMCP) which can include only viable human cells. In addition, human, animal, insect, or bacterial cell lines can be used as a substrate for the production of some biological drugs. The list of quality parameters and test methods for medicinal products quality control are specified in the State Pharmacopoeia of the Russian Federation, but it contains only a few general monographs on blood products and a few requirements for cell lines as substrates for the production of biological drugs (which cover all types of cells). Currently, there is no regulatory document comparable to the State Pharmacopoeia of the Russian Federation that would contain requirements and test methods for BMCP quality control in the Russian Federation. Thus, one of the issues that arises both during quality control and approval of BMCPs is the lack of a regulatory document defining requirements for BMCP quality parameters and test methods. However, some general monographs of the Russian Pharmacopoeia and other pharmacopoeias can be used for quality control of both cell lines and non-cellular components. The aim of the study was to analyse and compare different pharmacopoeial requirements for the quality of cell lines used as components in human cell- and tissue-based products (comparable to BMCPs), which could be used in BMCP quality control. The paper analyses general monographs of the United States Pharmacopoeia (USP), European Pharmacopoeia (Ph. Eur.), Japanese Pharmacopoeia, Pharmacopoeia of the Republic of Belarus, including general monographs on biological/biotechnological products, because their requirements apply to human cell lines included as components in products similar to BMCPs. The analysed approaches and methods of quality control of cell- and tissue-based products described in the USP and Ph. Eur. could form the basis for elaboration of general monographs for the Russian Pharmacopoeia, including identification, potency, viral safety, and mycoplasma tests that are based on the nucleic acid amplification technology and other tests for cell lines as components of BMCPs.